Orexin receptor antagonists as therapeutic agents for insomnia - Equihua, Ana C.; De La Herrán-Arita, Alberto K.; DRUCKER-COLIN, RENE (Frontiers in Pharmacology, 2013)
Insomnia is a common clinical condition characterized by difficulty initiating or maintaining sleep, or non-restorative sleep with impairment of daytime functioning. Currently, treatment for insomnia involves a combination of cognitive behavioral therapy and pharmacological therapy. Among pharmacological interventions, the most evidence exists for benzodiazepine receptor agonist drugs (GABAA receptor), although concerns persist regarding their safety and their limited efficacy. The use of these hypnotic medications must be carefully monitored for adverse effects. Orexin (hypocretin) neuropeptides have been shown to regulate transitions between wakefulness and sleep by promoting cholinergic/monoaminergic neural pathways. This has led to the development of a new class of pharmacological agents that antagonize the physiological effects of orexin. The development of these agents may lead to novel therapies for insomnia without the side effect profile of hypnotics (e.g. impaired cognition, disturbed arousal, and motor balance difficulties). However, antagonizing a system that regulates the sleep-wake cycle may create an entirely different side effect profile. In this review, we discuss the role of orexin and its receptors on the sleep-wake cycle and that of orexin antagonists in the treatment of insomnia.